PENGARUH PEMBERIAN PUPUK ECO ENZYME TERHADAP PERTUMBUHAN RUMPUT GAJAH (Pennisetum Purpureum) - Asnan Hamid Harahap; Adhona Bhajana Wijaya Negara (Bajang Institute, 2025)
Greens are one of the most important elements in fulfilling livestock needs to survive. One effort to provide high-quality greens is to cultivate feed plants from superior grass species. Elephant grass is one of the superior greens commonly given to livestock with the characteristics of stem segments and leaf structures that are easy to digest. Eco enzyme fertilizer can be applied directly in fulfilling nutrients so that it can accelerate and increase plant production so that it has the potential to increase the growth and production of elephant grass. The purpose of this study was to determine the effect of eco enzyme fertilizer on the productivity of elephant grass (Pennisetum purpureum). This study used a Completely Randomized Design (CRD) with four treatments and five replications. The concentration of eco enzyme fertilizer applied was P0 as a control, P1 eco enzyme 20 ml, P2 eco enzyme 30 ml and P3 eco enzyme 40 ml. The research parameters included plant height, number of leaves, fresh production and dry production of elephant grass. The results of the study showed that P3 had plant height (182.70 cm), number of leaves (12.90 strands), fresh production of elephant grass (1.64 kg) and dry production of elephant grass (0.49 kg), the highest and different between each treatment. The addition of eco enzyme fertilizer with a concentration of 40 ml (P3) gave the best results for plant height, number of leaves, fresh production and dry production of elephant grass and has the potential to be applied in larger quantities